Comparison of Ultrasound‐Guided Right Brachiocephalic and Right Subclavian Vein Cannulation in Adult Patients. (28th January 2019) - Sun, Xingwei; Bai, Xuming; Cheng, Long; Gu, Xingshi; Xia, Rui; Du, Xiaolong; Shi, Jianming; Chen, Qian; Jin, Yong
Abstract : Objectives: To compare ultrasound‐guided right brachiocephalic vein (BCV) central venous catheter (CVC) placement to right subclavian vein (SCV) CVC insertion in terms of the puncture success rate and complications. Methods: A retrospective review was performed for all adult patients who received an ultrasound‐guided CVC via the right BCV or right SCV access route between January 2016 and March 2018. The puncture success rates and procedure‐related complications were analyzed. Results: Data were analyzed from 755 adult patients who underwent 915 CVC insertions. The overall success rate was higher in the BCV group compared to that in the SCV group (98.99% versus 96.87%; P  = .019). The first‐attempt success rate was higher in the BCV group compared to that in the SCV group (96.64% versus 89.34%; P  < .001). Intraoperative complications were observed in 16 cases in the BCV group (2.68%) and in 12 cases in the SCV group (3.76%). The incidence rates of postprocedure complications were 5.20% in the BCV group and 6.58% in the SCV group and included catheter‐related infections and thrombosis. Conclusions: Ultrasound‐guided cannulation of the right BCV is an effective and safe method for CVC placement in adult patients and provides an additional option for catheter access.